Financial System and its Component, as Factors of Economic Development of Ukraine - Alekseyenko Lyudmyla, Kulyna Halyna, Vatslavskyi Oleh, Shevchuk Anton, Yazlyuk Borys (International Journal of Advanced Science and Technology, 2020)
The article describes the economic essence of the financial system and its component, as factors of economic development of the country, which are to use the totality of economic relations in the sphere of formation of the appropriate structure of the system of new financial interconnections in order to create the proper conditions for balanced economic development. It is determined that economic development is a whole series of transformations and it is important to strengthen the role of the state in regulating many processes, to improve the quality level of management of the fiscal and monetary systems and to increase the efficiency of their coordination.